Optimizing Micro-Enterprise Management in the Candi Community to Improve Well-Being and Business Sustainability - Jati, Kuat Waluyo; Jannah, Richatul; Rizkyana, Fitrarena Widhi; Pertiwi, Meilani Intan; Fatimah, Tiara Saharani (Universitas Negeri Semarang, 2025)
Ultra-micro enterprises (UMi) in Candi Sub District face fundamental challenges that hinder their business growth, including difficulties in determining an accurate cost of goods sold (COGS), weak financial management, low awareness of the importance of product branding, and limited business legality ownership. This community service program aimed to enhance the managerial capabilities of business owners through interactive training, direct mentoring, and continuous evaluation. The implementation methods included lectures, discussions, QnA sessions, simulations, and mentoring, carried out in three stages: needs analysis, training implementation (COGS and financial management, personal branding, and business legality), and follow-up evaluation and mentoring. The results show an increase in participants' ability to calculate COGS by considering all production costs, which is reflected in a 20.6% increase in understanding based on the pre-post test, as well as the application of simple financial management through the practice of separating business and personal finances which has begun to be implemented by 35 participants. Participants were also able to build a more professional brand identity by developing logos, taglines, packaging, and consistent social media strategies. Additionally, there was an increased awareness of the importance of business legality as a gateway to financing and broader market opportunities. This program has had a positive impact on participants’ professionalism, competitiveness, and business sustainability, and it has the potential to serve as a model for empowering similar business communities.